Pengaruh Diskon, Promosi dan Kepercayaan Konsumen terhadap Keputusan Pembelian pada Penggunaan Aplikasi Shopee (Studi kasus pada masyarakat Banda Aceh) - Nara Pristiwa; Riwanul Nasron; Elma Yuliatul Luthfi Fani; Natasya Amelia Fatiha (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The development of business today is greatly influenced by information technology. The advancement of technology significantly affects consumer purchasing decisions. As we know, in the current era, many online sites offer online sales. It can be assured that online shopping is increasingly favored by consumers. Shopee is one of the most popular online shopping sites. Shopee offers many discounts at certain times, along with very attractive promotions that entice consumers to shop on Shopee. This study aims to determine the influence of discounts, promotions, and consumer trust on purchasing decisions when using the Shopee app. The research method used is an associative method with the goal of observing the influence or relationship between two or more variables in a study. The data analysis technique in this research is multiple linear regression analysis. The sample for this study consists of 96 respondents, while the data collection uses questionnaires. The data processing in this study uses SPSS. The results of this study indicate that discounts have a significant partial effect on purchasing decisions, promotions have a partial effect on purchasing decisions, and consumer trust partially affects purchasing decisions. Meanwhile, discounts, promotions, and consumer trust simultaneously influence purchasing decisions.